Adaptations to endurance vs strength training in elite athletes revealed by serum proteomics - Kiliç, H. B.; Ekiz, M. S.; Akin, S.; Çelikbiçak, Ö.; Tokgözoglu, L.; Kocaefe, Y. Ç. (Journal of Science and Medicine in Sport, 2026)
Objectives Elite training induces profound physiological adaptations, yet whether these changes manifest as stable circulating proteomes remains unclear. This study characterized serum proteomic profiles in male and female Olympic-level athletes to identify biomarkers associated with long-term endurance and strength training.